Induction of Wnt signaling antagonists and p21-activated kinase enhances cardiomyocyte proliferation during zebrafish heart regeneration. (16th September 2020) - Peng, Xiangwen; Lai, Kaa Seng; She, Peilu; Kang, Junsu; Wang, Tingting; Li, Guobao; Zhou, Yating; Sun, Jianjian; Jin, Daqing; Xu, Xiaolei; Liao, Lujian; Liu, Jiandong; et al.
Abstract: Heart regeneration occurs by dedifferentiation and proliferation of pre-existing cardiomyocytes (CMs). However, the signaling mechanisms by which injury induces CM renewal remain incompletely understood. Here, we find that cardiac injury in zebrafish induces expression of the secreted Wnt inhibitors, including Dickkopf 1 (Dkk1), Dkk3, secreted Frizzled-related protein 1 (sFrp1), and sFrp2, in cardiac tissue adjacent to injury sites. Experimental blocking of Wnt activity via Dkk1 overexpression enhances CM proliferation and heart regeneration, whereas ectopic activation of Wnt8 signaling blunts injury-induced CM dedifferentiation and proliferation. Although Wnt signaling is dampened upon injury, the cytoplasmic β-catenin is unexpectedly increased at disarrayed CM sarcomeres in myocardial wound edges. Our analyses indicated that p21-activated kinase 2 (Pak2) is induced at regenerating CMs, where it phosphorylates cytoplasmic β-catenin at Ser 675 and increases its stability at disassembled sarcomeres. Myocardial-specific induction of the phospho-mimetic β-catenin (S675E) enhances CM dedifferentiation and sarcomere disassembly in response to injury. Conversely, inactivation of Pak2 kinase activity reduces the Ser 675-phosphorylated β-catenin (pS675-β-catenin) and attenuates CM sarcomere disorganization and dedifferentiation. Taken together, these findings demonstrate that coordination of Wnt signaling inhibition and Pak2/pS675-β-catenin signaling enhances zebrafish heart regeneration by supporting CM dedifferentiation and proliferation.